Nicknames of English-Speaking Adolescent Users of Social Networks (on the Example of Twitter) - V. V. Kaziaba; D. E. Barmina (Научный диалог, 2020)
The features of the self-nomination of English-speaking adolescents in Internet communication - in a social network such as Twitter microblogging are discussed in the article. The focus of the article is the anthroponymic units of Internet communication - nicknames belonging to Internet users of the age group of 12-17 years. The relevance of the study is determined by the need to fill up research gaps in socio-, psycho- and ontolinguistics, as well as the unflagging attention of philologists to the anthropocentric aspects of Internet communication. The novelty lies in an integrated approach to the consideration of the features, methods and means of naming teenagers on Twitter. The nominative potential of nicknames is analyzed. In accordance with the nature of the constitutive token, self-nomination groups of autonomous, pseudonymous, and transitional types are distinguished. Conclusions are drawn about the characteristics of the anonymity of teenage names on Twitter (the degree of anonymity and its expressiveness). The authors also dwell on the structural aspect of virtual individual names, identifying the most productive models of property creation in virtual space. The results of a graphical analysis of the research material are presented, accompanied by a quantitative characteristic of paraverbal means. The analysis has established a correlation between the psychological new formations of adolescents and the characteristics of their nicknames on Twitter. It is shown that the inconsistency and originality of the considered stage of the ontogenetic development of users is projected onto their self-nomination.